FAKTOR RISIKO STUNTING PADA ANAK USIA 0—23 BULAN DI PROVINSI BALI, JAWA BARAT, DAN NUSA TENGGARA TIMUR - Nadiyah, Nadiyah; Briawan, Dodik; Martianto, Drajat (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The purpose of this study was to assess the prevalence and the risk factors of stunting among 0—23 month old children in Bali, West Java, and East Nusa Tenggara. The data was gathered from Basic Health Research 2010, Ministry of Health Republic of Indonesia. Basic Health Research 2010 was a cross-sectional survey. The Three provinces i.e Bali, West Java, and East Nusa Tenggara were selected as they had a mild, moderate, and severe levels of stunting among children aged less than five years, respectively. A total of 1 554 children aged 0—23 months were selected in the analysis. Prevalence of stunting in Bali, West Java, and East Nusa Tenggara was 35.9%, 31.4% and 45.0%, respectively. Chi-square test revealed that there are positive and significant associations between low birth weight, poor sanitation, paternal smoking in the house, low level of maternal and paternal education, low income, and mother’s height less than 150 cm with stunting among 0—23 months old children (p<0.05). Logistic regression test showed that the risk factors for stunted children were low birth weight (OR=2.21; 95%CI:1.006—4.860), mother’s height less than 150 cm (OR=1.77; 95%CI:1.205—2.594), poor sanitation (OR=1.46; 95%CI:1.010—2.126) and prelacteal feeding (OR=1.47; 95%CI:1.000—2.154). The stunting reduction should be initiated from improving the quality of antenatal care and basic neonatal care, specifically counseling of exclusive breastfeeding.